An In0.53Ga0.47As/In0.52Al0.48As/In0.53Ga0.47As double hetero-junction junctionless TFET. (10th June 2021) - Liu, Hu; Yang, Lin-An; Zhang, Huawei; Zhang, Bingtao; Zhang, Wenting
Abstract: In this paper, an In0.53 Ga0.47 As/In0.52 Al0.48 As/In0.53 Ga0.47 As double hetero-junction junctionless tunnel field-effect transistor (JL-TFET) is proposed, whose N + -channel is formed through the two-dimensional electron gas (2DEG) generated by the hetero-junction without directly implementing physical doping. It can not only effectively suppress the random dopant fluctuation in traditional JL-TFET, but also solve the problem that the electron tunneling is hindered by the wide tunneling barrier at the tunneling junction in conventional dopingless TFET. The existence of 2DEG at the source/channel junction for the proposed JL-TFET can decrease the lateral tunneling distance and enlarge the energy range for tunneling, thereby promoting the device performance. Investigations on effects of the thickness of channel layer ( T c ), the N-type doping concentration (N + D) in doping layer, and the gate dielectric on JL-TFET demonstrate that the optimal device characteristics can be obtained when T c  = 2 nm, N + D = 1 × 10 19 cm −3, and the high-K dielectric is adopted.